Capturing dynamism in women’s roles in an agrarian economy: A study in the Eastern Gangetic Plains of India - Bhattacharya, Prateek Madhab; Bhattacharya, K.K.; Das, T.; Dhar, T.; Ghosh, A.; Chowdhury, A.K.; Sen, S.; Jackson, T. (Uttar Banga Krishi Viswavidyalaya, 2023)
Research suggests that investing in women’s economic empowerment has important linkages with gender equality, poverty eradication, and inclusive growth. Considering women’s share of 31% of the total agricultural workforce in India, changes in terms of involvement in operations and decision-making can have a significant impact on trajectories of economic empowerment. A study was undertaken in northern West Bengal during 2020–21, covering 687 randomly selected respondents, to understand the perceptions of the agrarian population regarding these changes and the foresight of transformations in gender roles. Exploratory analysis was carried out to understand the changes that have occurred regarding women’s roles in the farm economy, and to explore what they expect to happen in the future. Our study indicates that about 69% of respondents expect enhanced participation of farm women in agriculture within 5–10 years, with a gradual change from their nominal participation in the past, to most activities in the future, mainly due to outmigration of males from farm families. Similarly, about 35% of the respondents believe that women’s roles in decision-making will increase in the future. Assumption of the role of functional head (in the absence of a male head) and prominence of the nuclear family are two major facts to enforce this paradigm shift in decision-making. This paper will identify key elements that can contribute positively to this shift. Enhanced participation and an increased role in decision-making can lead to a more inclusive farm economy as a whole but warrants necessary initiatives to support the transition.